Combination of PB2 271A and SR polymorphism at positions 590/591 is critical for viral replication and virulence of swine influenza virus in cultured cells and in vivo - Liu, Qinfang; Qiao, Chuanling; Marjuki, Henju; Bawa, Bhupinder; Ma, Jingqun; Guillossou, Stephane; Webby, Richard J.; Richt, Juergen A.; Ma, Wenjun (My University, 2011)
Triple reassortant swine influenza viruses (SIVs) and 2009 pandemic H1N1 (pH1N1) virus contain an avian-origin PB2 with 271A, 590S, 591R, and 627E. To evaluate the role of PB2 271A, 590S, and 591R in the replication and virulence of SIV, single (1930-TX98-PB2-271T)-, double (1930-TX98-PB2-590A591A)-, and triple (1930-TX98-PB2-271T590A591A)-mutated viruses were generated in the background of the H1N1 A/swine/Iowa/15/30 (1930) virus with an avian-origin PB2 from the triple-reassortant A/swine/Texas/4199-2/98 (TX98) virus, called the parental 1930-TX98-PB2. Compared to parental virus and single- and double-mutated viruses, the triple-mutated virus replicated less efficiently in cell cultures and was attenuated in mice. These results suggest that a combination of 271A with the 590/591 SR polymorphism is critical for pH1N1 and triple-reassortant SIVs for efficient replication and adaptation in mammals.
Keywords: Swine influenza virus; PB2; 271A; 590/591 SR polymorphism; Replication and virulence; Cultured cells; In vivo